Cambios post mortem en mucosa intestinal y tejido pulmonar de Mus musculus, observados al microscopio electrónico de barrido - Kozuka, Yoshimichi (1981)
Post mortem ultrastructural alterations of surface epithelial tissues were studied by scanning electron microscopy. Ten male albino mice were sacrificed, and the duodenum, ileum arid lung excised and fixed immediately, at 20, 40, 60 and 120 minutes post mortem. Thdntestinal villi and mierovilli tended to flatten and to lose rigidity of cellular architecture. Alveolal epithelial cells showed the oeginning of edema. Ultrastructural changes in epithelial cells were noticed as early as 20 minutes after death.